Virtuelles Interview mit Robert Guttmann - O'Connor, James (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
The Asian crisis and the US interests in dealing with the crises are analyzed. The crisis itself is much more than only a financial crisis. It may indicate a new phase in the evolution of capitalism, the emergence of a more competitive capitalism organized on a global level.